Mortality Records of the Irrawaddy Dolphin Orcaella brevirostris (Artiodactyla: Delphinidae) in Sumatra and Java - Nur Rachman; Muhammad Sayidina Ali; Randi Syafutra; Surianto Effendi; Sahat Aritonang; Muhammad Iqbal (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2026)
Indonesia is a global biodiversity hotspot, yet aquatic mammals remain understudied, particularly in coastal and estuarine ecosystems. The Irrawaddy Dolphin Orcaella brevirostris inhabits these environments and is highly exposed to anthropogenic pressures. This study compiles mortality records of O. brevirostris in Sumatra and Java using published papers, media reports and citizen science data. A total of 24 records (2011–2025) were documented, with most concentrated along the eastern coast of Sumatra. Of the 24 documented mortality records of O. brevirostris in Sumatra and Java (2011–2025), unknown causes accounted for the majority of deaths (14 records, 58.3%). Fishing gear entanglement was the second most common cause (7 records, 29.2%), representing the primary identified anthropogenic threat. The remaining mortalities were each attributed to suspected poaching, strong monsoon currents, and extreme weather (1 record each, 4.2%). Reported body lengths ranged from 90 to 225 cm and weights from 80 to 150 kg. Both juvenile and adult individuals were affected, with adult mortality raising concerns for population viability. These findings highlight critical risk zones and the need for improved monitoring and conservation measures.